2018
DOI: 10.1002/adfm.201807094
|View full text |Cite
|
Sign up to set email alerts
|

Hole‐Transporting Materials Incorporating Carbazole into Spiro‐Core for Highly Efficient Perovskite Solar Cells

Abstract: Hole‐transporting materials (HTMs) play a significant role in hole transport and extraction for perovskite solar cells (PeSCs). As an important type of HTMs, the spiro‐architecture‐based material is widely used as small organic HTM in PeSCs with good photovoltaic performances. The skeletal modification of spiro‐based HTMs is a critical way of modifying energy level and hole mobility. Thus, many spiro alternatives are developed to optimize the spiro‐type HTMs. Herein, a novel carbazole‐based single‐spiro‐HTM na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 67 publications
1
54
0
1
Order By: Relevance
“…Understanding the structure‐property relationship of HTM is a precondition for the rational designing of new HTMs . Liao et al., designed and synthesized a new HTM SCZF‐5 via varying from SAF core to SCZF core likewise comparing with the classic 9,9′‐spirobifluorene structure, they find that the PSC based on new HTM shows higher PEC than the commercial HTM spiro‐OMeTAD . Gao et al.…”
Section: Introductionmentioning
confidence: 95%
“…Understanding the structure‐property relationship of HTM is a precondition for the rational designing of new HTMs . Liao et al., designed and synthesized a new HTM SCZF‐5 via varying from SAF core to SCZF core likewise comparing with the classic 9,9′‐spirobifluorene structure, they find that the PSC based on new HTM shows higher PEC than the commercial HTM spiro‐OMeTAD . Gao et al.…”
Section: Introductionmentioning
confidence: 95%
“…After that, high PCEs of 16.91% and 18.92% were accomplished in PSCs by using the methoxydiphenylamine substituted carbazole as HTMs in 2016 and 2018, respectively, as reported by Nazeeruddin, Getautis and Snaith et al Most recently, Sellinger and Snaith et al reported PCEs over 18% and >1000 h operational stability by applying a lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)‐free carbazole‐based HTM, ET44, in PSCs . Although promising device performance in PSCs have been verified with carbazole‐based HTMs, the PCEs of related devices still cannot rival the efficiency rendered by the well‐known HTM‐Spiro‐OMeTAD (2,2′,7,7′‐tetrakis‐( N , N ‐di‐ p ‐methoxy‐phenyl‐amine)9,9′‐spirobifluorene) in PSCs . Particularly, the fundamental understanding of the impact of linking topology on the properties of carbazole‐based HTMs is lacking, and such knowledge is vital for future design concepts for even more efficient carbazole‐based HTMs for the application in high‐performance ssMSCs.…”
Section: Introductionmentioning
confidence: 73%
“…[23][24][25] Carbazol unit provides a wide range of charge transport molecules, such as carbazole-based HTMs with triphenylamine moieties, which have been explored as promising candidates for highperforming perovskite solar cells. [26][27][28] Moreover, carbazole compounds are very relevant in developing phosphorescent organic light-emitting diodes (PHOLEDs), where these compounds act as the host materials, mainly due to their high triplet state energy and excellent hole transport capability. [29][30][31] Among the carbazole-based compounds, the 4,4 0 -bis(N-carbazolyl)-1,1 0 -biphenyl (CBP) and 1,3-bis(N-carbazolyl)benzene (mCP) have seen wide use in PHOLEDs, with interesting results in light-emitting cells.…”
Section: Introductionmentioning
confidence: 99%